2006
DOI: 10.1093/jmedent/43.3.498
|View full text |Cite
|
Sign up to set email alerts
|

Anopheles gambiae(Diptera: Culicidae) Oviposition in Response to Agarose Media and Cultured Bacterial Volatiles

Abstract: Anopheles gambiae s.s. Giles accepted a range of agarose gels, varying from 0.5 to 8% (wt:vol), for oviposition; laid more eggs on 0.5% agarose gels than on moist filter paper or on drier agarose; and laid equal numbers of eggs on 0.5% agarose gels and distilled water. Larvae hatched on agarose gel substrates and crawled onto the surface of moist agarose gels, but they tended only to burst the egg cap and remain within the egg case on drier gels. A mixture of cultured bacteria, originating from a natural larva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 42 publications
(40 citation statements)
references
References 23 publications
0
34
0
1
Order By: Relevance
“…In binary choice assays, Ponnusamy et al (2008) demonstrated that microorganisms in leaf infusions produced oviposition-stimulating kairomones, but also that bacteriaassociated carboxylic acids and methyl esters serve as potent oviposition stimulants for gravid Aedes aegypti. In contrast, the results obtained by Huang et al (2006) suggested that some bacterial odours may be repellent for Anopheles gambiae since a mixture of cultured bacteria (Pseudomonas strains) originating from the natural larval habitat (soil and water surfaces) significantly reduced the oviposition. Maw (1970) reported that bacteria of the family Pseudomonaceae produced decanoic acid and rendered rearing water attractive to Culex restuans.…”
Section: Culicidaementioning
confidence: 88%
“…In binary choice assays, Ponnusamy et al (2008) demonstrated that microorganisms in leaf infusions produced oviposition-stimulating kairomones, but also that bacteriaassociated carboxylic acids and methyl esters serve as potent oviposition stimulants for gravid Aedes aegypti. In contrast, the results obtained by Huang et al (2006) suggested that some bacterial odours may be repellent for Anopheles gambiae since a mixture of cultured bacteria (Pseudomonas strains) originating from the natural larval habitat (soil and water surfaces) significantly reduced the oviposition. Maw (1970) reported that bacteria of the family Pseudomonaceae produced decanoic acid and rendered rearing water attractive to Culex restuans.…”
Section: Culicidaementioning
confidence: 88%
“…gambiae species complex, and are the two principal malaria vectors across sub-Saharan Africa. Many aspects of behavior of the mosquitoes have been studied and well documented (Gillies and Coetzee 1987;Huang et al 2005Huang et al , 2006, but little is known about their oviposition behavior under field conditions (Chen et al 2006a). Better understanding of breeding behavior of mosquitoes may provide novel avenues for ecological control of mosquitoes and mosquito-borne disease (Pates and Curtis 2005).…”
Section: Introductionmentioning
confidence: 99%
“…Some sites contain large amounts of anopheline larvae, while many others are vacant despite high densities of mosquito adults in surrounding houses (Minakawa et al 1999(Minakawa et al , 2001). This phenomenon leads to speculation that some aquatic sites are more suitable or attractive for oviposition (McCrae 1984;Huang et al 2005Huang et al , 2006 and/or more favourable for larval development than others (Minakawa et al 1999). If this is true, individual aquatic sites that contain anopheline larvae may be the result of oviposition by multiple females, especially during a dry season when suitable breeding habitats are limited.…”
Section: Introductionmentioning
confidence: 99%
“…gambiae is commonly found in association with grasses, but it was not clear whether presence of larvae in such habitats results from hatched eggs laid on or around wet grasses, or whether larvae were carried there by flowing water. This question has been addressed in laboratory oviposition choice experiments by Huang et al [65]. They found that An.…”
Section: Vegetationmentioning
confidence: 99%